Remediation of industry waste water effluent by using kenaf as waves absorbent - Wong Yee Ching; S.H. Lim; N.A. Atiqah (2013)
Batik industry is one of the industries that produce high amount of waxes in their wastewater. Natural fiber has become apparently important as a source of absorbent. Kenaf (Hibiscus cannabinus) core is one of the good absorbent to absorb the waxes due to its characteristic. The contact time, weight of kenaf and the different form of kenaf can effect its absorbency. The powder form of kenaf has been proven to have better performance in term of absorption. The most suitable contact time is 15 minutes in which it has the highest wax absorption. Moreover, 1.2g of fibrous kenaf and 0.8g till 1.2g of kenaf powder showed high wax absorption capacity.